The Retreats of Thought : Poems - Cherry, Kelly (Book collections on Project MUSE., 2009)
In this book-length sonnet sequence, Kelly Cherry explores the philosophical domain, addressing classic questions, raising new ones, and sometimes doing philosophy in fourteen lines. A former philosophy student in graduate school, she retains a deep love of philosophical inquiry and maintains that our lives are intimately bound to the philosophical choices we make. Conscious study of our choices, Cherry believes, can lead to greater freedom. Passionate, skeptical, witty, and sometimes wry, these succinct poems concern themselves with very large matters--the nature of time, the definitions of go.